Comparison of the Repeatability of Macular Vascular Density Measurements Using Four Optical Coherence Tomography Angiography Systems - Jingyuan Yang; Mingzhen Yuan; Erqian Wang; Youxin Chen (Journal of Ophthalmology)
The aim of this study was to compare the repeatability of optical coherence tomography angiography (OCT-A) measurements of macular vessel density using four OCT-A systems, including Heidelberg Spectralis HRA, Optovue RTVue XR, Zeiss Cirrus HD-OCT 5000, and Topcon DRI OCT Triton. A cross-sectional design was used for this study. The vascular density and vascular length density of the superficial and deep retinal capillary plexuses were imaged with OCT-A using 3 mm and 6 mm scan patterns and were calculated using ImageJ. Comparisons of intraclass correlation coefficients (ICC) were conducted. We found that the OCT-A systems had various levels of repeatability. Zeiss had better repeatability for vessel density than the other systems (overall ICC = 0.936). Optovue had better repeatability for vessel length density when the 6 mm scan pattern was used (ICC = 0.680 and 0.700 for retinal superficial and deep capillary plexus, respectively). We concluded that repeatability varied when different scan patterns of various OCT-A systems were used for imaging the superficial retinal and deep capillary plexuses. Results should be seen as valid only for a given method. The repeatability of various OCT-A systems should be considered in clinical practice and in clinical trials that use OCT-A metrics as outcome measures.